aktor-Faktor Yang Berhubungan Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di Rumah Sakit Tk II 03.05.01 Dustira - Dedi, Dedi Supriadi; Evangelina, Evangelina H (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2019)
Chronic renal disease may cause the irreversible decline of the function of the kidneys needing therapy inthe form of a transplant or hemodialysis.It may affect the quality of life of the patient, with many factorscontributing to the effect, such as gender, age, education background, occupation, and the duration ofhemodialysis and anemia. The study aims to explore factors related to the quality of life of chronic renal diseasepatients undergoing hemodialysis at Dustira Hospital.It employed the analytical survey method with a crosssectionalapproach.It involved all patients undergoing regular hemodialysis treatment at the UnitHemodialisaDustira Hospital (II.03.05.01) in 2018, with 37 samples fulfilling the inclusion criteria forconsecutive sampling. The data was gained directly from the patients as well as their medical records.The dataanalysis used the uni-variate and bi-variate techniques via the chi-square test. The results showed there were nofactors (namely gender, age, education background, occupation, and the duration of the treatment) with the pvalueof ≥ 0.05.It is recommended that Dustira Hospital offers counseling services and sharing programs for patients to share their experiences.Further investigations may be carried out to address more complex issuesregarding the most influential factors in the quality of life.